Play Fairway Analysis Retrospective GeoRePORTs - Kolker, Amanda; Taverna, Nicole; Pauling, Hannah (National Renewable Energy Laboratory, 2020)
NREL, as part of the Play Fairway Analysis (PFA) Retrospective and with assistance from PFA PIs, completed GeoRePORTs for the sites identified in Phases 1&2 of the DOE PFA projects. The GeoRePORT (geothermal resource portfolio optimization and reporting technique) uses two factors to describe a specific project; grade and project readiness level. Grade describes the quality or potential of a project while project readiness level shows the progress of research and development. The categories that factor into the total grades and readiness levels are Geological, Technical, and Socio-Economic.
Keywords: geothermal; energy; PFA; GeoRePORT; SRP; Snake River Plain; Idaho; blind; resource; characterization; Washington; MSHSZ; MSH-N; WRV; Wind River Valley; Mount St. Helens; Shear Zone; North; Washington State; play fairway analysis; Hawaii; Lanai; Mauna Kea; EGB; Eastern Great Basin; Twin Peaks; Utah; Cove Fort; Crater Knoll; Mountain Home; Nevada; Nevada Great Basin; Granite Springs Valley; Northern; Sou Hills; Crescent Valley; Southern Gabbs Valley; Tularosa Basin; New Mexico; ADF-SW/NASA; ADF; Aerospace Data Facility; Fort Bliss; McGregor Range; WSMR; White Sands Missile Range; Mount Baker; Camas Prairie; permeability; drilling; logistics; market; transmission; land access